Night Flying Insect Density and Activity Pattern in Bau, Lundu & Serian, Sarawak. - Siti Amirah, Abdul Ghani (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Many researches have been conducted to address the impacts of urbanisation on diversity and density of insects in temperate regions but not in tropical regions. This study was conducted from October 2014 until April 2015 in order to determine the insect density and activity pattern of night flying insects in Bau, Lundu and Serian. Insect sampling was conducted by towing a trap with 1 m2 opening using a vehicle over a distance of 1000 m. A total of 1372 individuals were captured during the sampling period. The density of night flying insects in Bau, Lundu and Serian was 0.423 individuals/m3, 0.600 individuals/m3 and 0.349 individuals/m3 respectively. The main orders of insects sampled are Diptera followed by Coleoptera, Hymenoptera, Herniptera, Lepidoptera and Orthoptera. Peak time of those insects' activities is between 1830-1930 hours. This study also showed that there is a significant difference between Bau, Lundu and Serian in term of density but no difference in the activity pattern.